Integral estimation of labour of long distance phone service employees (Experimental biology, 2015)
Examine the hygienic conditions of work, organization, nature and characteristics of the production process telephonelong distance telephone service; To investigate the physiological reactions of the organism in the performance of key manufacturing operations and to provide an ergonomic assessment of the relationship telephones and production equipment in the process of labor; Examine the functional state of workers - performance, neuro-emotional tension, fatigue - inthe dynamics of the major shifts depending on the volume of information load; To assess the severity and intensity of labor telephones various departments; To develop comprehensive measures to optimize the work of employees long-distance telephone service and health promotion telephone operators. 1.Usloviya labor central telephone service are characterized by the formation of the complex adverse vocational factors of production, among which the most important are the lowfrequencynoise, and electromagnetic fi elds, microclimate parameters and stress. 2. During the working day at the telephone operators during the term development in the morning shift lengthening of the latent period of visual-motor reaction to red and white light, sluhomotornoy reaction of sound, increased run-time concentration.
Keywords: adverse working conditions; workability; fatigue factor